PROBLEMS OF ENSURING THE INTEGRATION OF PEDAGOGICAL SOFTWARE WITH CLOUD TECHNOLOGIES (IN THE EXAMPLE OF M-LEARNING) - Jurayev, Tuychi (THE INNOVATION ECONOMY, 2026)
The article discusses the problems and solutions to ensure the integration of pedagogical software with cloud technologies using examples from mobile educational programs that are currently used in practice